Ceilometer calibration for retrieval of aerosol optical properties. (March 2015) - Jin, Yoshitaka; Kai, Kenji; Kawai, Kei; Nagai, Tomohiro; Sakai, Tetsu; Yamazaki, Akihiro; Uchiyama, Akihiro; Batdorj, Dashdondog; Sugimoto, Nobuo; Nishizawa, Tomoaki
Abstract: Ceilometers are durable compact backscatter lidars widely used to detect cloud base height. They are also useful for measuring aerosols. We introduced a ceilometer (CL51) for observing dust in a source region in Mongolia. For retrieving aerosol profiles with a backscatter lidar, the molecular backscatter signal in the aerosol free heights or system constant of the lidar is required. Although the system constant of the ceilometer is calibrated by the manufacturer, it is not necessarily accurate enough for the aerosol retrieval. We determined a correction factor, which is defined as the ratio of true attenuated backscattering coefficient to the measured attenuated backscattering coefficient, for the CL51 ceilometer using a dual-wavelength Mie-scattering lidar in Tsukuba, Japan before moving the ceilometer to Dalanzadgad, Mongolia. The correction factor determined by minimizing the difference between the ceilometer and lidar backscattering coefficients was approximately 1.2±0.1. Applying the correction to the CL51 signals, the aerosol optical depth (AOD) agreed well with the sky-radiometer AOD during the observation period (13–17 February 2013) in Tsukuba ( 9 × 10 − 3 of mean square error). After moving the ceilometer to Dalanzadgad, however, the AOD observed with the CL51 (calibrated by the correction factor determined in Tsukuba) was approximately 60% of the AErosol RObotic NETwork (AERONET) sun photometer AOD. The possible causes of the lower AOD results are as follows: (1) the limited height range of extinction integration ( < 3 km ); (2) change in the correction factor during the ceilometer transportation or with the window contamination in Mongolia. In both cases, on-site calibrations by dual-wavelength lidar are needed. As an alternative method, we showed that the backward inversion method was useful for retrieving extinction coefficients if the AOD was larger than 1.5. This retrieval method does not require the system constant and molecular backscatter signals, and can be applied to severe dust and air pollution aerosol cases in East Asia. Abstract : Highlights: Determine a correction factor for the calibration of ceilometer signals. The corrected AODs agreed well with the sky-radiometer AODs. The correction factor can vary during transportation or window contamination. Backward inversion is useful for retrieving extinction if AOD is larger than 1.5.